Peran Efikasi Diri, Pola Asuh Otoritatif, dan Motivasi Berprestasi terhadap Kematangan Karir - Safaria, Triantoro (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Abstract. Career maturity is an important aspect that should be achieved by the individual. Â Underdeveloped of career maturity will result in hesitancy in deciding his career, which then would hinder the achievement of a career in the future. This study was aimed to test whether self-efficacy, achievement motivation, and authoritative parenting has contributed to the maturity of an individual's career. Additionally, this study also examined whether there is difference in career maturity between male with female students. A total of 214 psychology students were participated in this study. The results showed self-efficacy, achievement motivation, and authoritative parenting contribute to student career maturity. However, no significant difference was found on career maturity between male and female students. Other results found that achievement motivation has the greatest contribution to the career maturity.Â Keywords: Career maturity, self efficacy, need of achievement, authoritarian parenting, and students